![- \frac{7}{8} k](https://tex.z-dn.net/?f=-%20%5Cfrac%7B7%7D%7B8%7D%20k)
= 21
First, simplify
![\frac{7}{8} k](https://tex.z-dn.net/?f=%20%5Cfrac%7B7%7D%7B8%7D%20k)
to
![\frac{7k}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B7k%7D%7B8%7D%20)
/ Your problem should look like:
![-\frac{7k}{8}](https://tex.z-dn.net/?f=%20-%5Cfrac%7B7k%7D%7B8%7D%20)
= 21
Second, multiply both sides by 8. / Your problem should look like: -7k = 167
Third, divide both sides by -7. / Your problem should look like: k =
Fourth, simplify
![\frac{168}{-7}](https://tex.z-dn.net/?f=%20%5Cfrac%7B168%7D%7B-7%7D%20)
to
![\frac{168}{7}](https://tex.z-dn.net/?f=%20%5Cfrac%7B168%7D%7B7%7D%20)
/ Your problem should look like: k =
Fifth, simplify
![\frac{168}{7}](https://tex.z-dn.net/?f=%20%5Cfrac%7B168%7D%7B7%7D%20)
to 24. / Your problem should look like: k = -24
Answer:
k = -24
1. 24%
2. 13%
3. 60%
1. Since 6/25 is .24, 24% of the class was absent
2. He spent 3 hours in total.. Divide is by 24 because there are 24 hours in a day. 3/24 is 0.125 for 13% of the day
3. He ran 3 of the 5 miles, so 3/5 = 0.6.. meaning 60%. The time doesn’t matter
Do you know it in English because then i can help<span />
Based on the given summation notation, the expression that shows one way to simplify 43 Σ n=1 (3+9n) is (a) 43 Σ n=1 3 + 43 Σ n=1 9n
<h3>How to determine the summation expression?</h3>
The expression is given as:
43Σn=1(3+9n)
As a general rule, if a summation notation is represented using the following expression
Σ(a + bn)
The equivalent expression of the above summation notation is
Σa + bn
Where the variable a is a constant in the expression
This means that:
Σ(a + bn) = Σa + bn
Using the above equation as a guide, we have the following equivalent equation
43 Σ n=1 (3+9n) = 43 Σ n=1 3 + 43 Σ n=1 9n
Hence, based on the given summation notation; the expression that shows one way to simplify 43 Σ n=1 (3+9n) is (a) 43 Σ n=1 3 + 43 Σ n=1 9n
Read more about summation notation at:
brainly.com/question/16599038
#SPJ1
Answer:A polynomial added to a polynomial also still gives a polymonial